THE IMPLICATION OF EXTRINSIC MOTIVATION TOWARDS THE LIBRARIAN INTENTION TO ACCEPT RESOURCES DESCRIPTION AND ACCESS (RDA) IN MALAYSIA - Abd Latif Abdul Rahman; Zati Atiqah Mohamad Tanuri; Tengku Rafidatul Akma Tengku Razali, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The evolution of the information environment towards the digital environment has changed the cataloging standards towards Resource Description and Access (RDA) standards. Hence, this study aims to investigate Malaysian Librarian’s intention to accept RDA based on extrinsic motivation factors. Questionnaires were used to gather data from respondents who are the librarians from National Library of Malaysia. The data were analyzed using SPSS and SmartPLS and the results show that only TFC influenced the librarian's intention to accept RDA rather than PE, EE, and RE. The result of the findings was discussed and some recommendations were proposed.